2016
DOI: 10.1136/annrheumdis-2016-210482
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity and left ventricular systolic function in rheumatoid arthritis

Abstract: Disease activity and left ventricular systolic function in rheumatoid arthritisWe have read with interest the recent paper by Midtbø et al. 1The authors evaluated 119 patients with rheumatoid arthritis (RA), and found that patients with RA active disease (Simplified Disease Activity Index (SDAI) >3.3) compared with those in remission (SDAI<3.3) had lower left ventricular (LV) systolic myocardial function, assessed by stress-corrected mid-wall shortening (scMWS) and global longitudinal strain (GLS).Data from Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…Further, we found that this association was independent of the presence of a normal ejection fraction and traditional cardiovascular risk factors like hypertension and smoking. In a letter to the editor, Giollo et al 1 present data from a series of 235 patients with RA 3. In contrast to our findings, Giollo et al 1 did not find an association between RA disease activity and LV systolic myocardial function when assessed by scMWS or tissue Doppler mitral annular systolic velocity (S´), despite a much higher median RA disease activity in their population 3.…”
contrasting
confidence: 90%
“…Further, we found that this association was independent of the presence of a normal ejection fraction and traditional cardiovascular risk factors like hypertension and smoking. In a letter to the editor, Giollo et al 1 present data from a series of 235 patients with RA 3. In contrast to our findings, Giollo et al 1 did not find an association between RA disease activity and LV systolic myocardial function when assessed by scMWS or tissue Doppler mitral annular systolic velocity (S´), despite a much higher median RA disease activity in their population 3.…”
contrasting
confidence: 90%